CERIF Tutorial: Part 2 - Dvořák, Jan (2018)
Interoperability: 1. Agreed Semantics, 2. Agreed Format, 3. Agreed Protocol. CERIF XML Interchange Format: XML Schema, Based on the ER model, Undergone a big update. CERIF Profiles in general: Useful subsets of CERIF for specific research information interchange scenarios